Afirmasi Reformed Injili terhadap Teologi Natural - Hendra Yohanes (VERBUM CHRISTI JURNAL TEOLOGI REFORMED INJILI, 2023)
Does Reformed theology necessarily imply vehement objections to natural theology? Do the Reformed Christians need to despise the natural theology at all? This article argues that "the book of nature" will establish the historical-theological foundation for appreciating the general revelation in the creation and affirming natural theology. In order to get the argument, it will summarize the historical overview of liber naturae in Christianity and the Reformed tradition. Subsequently, the Reformed Evangelical perspective is a tool of theological arguments in responding to the objections to natural theology. Following the Reformed theology and Evangelicalism, the book of nature should be read in the spectacles of the Holy Scripture. Natural theology is also affirmed as a preparatory step in the gospel proclamation.